Teacher Assessment to School Readiness on the 5-6 Year-Old Children in State Kindergarten in Pekanbaru (Motoric Physical, Social Emotional, Moral, Language, and Cognitive Aspect) - Daviq Chairilsyah; Rita Kurnia (Journal of Educational Sciences, 2018)
This research is to know teacher's assessment on school readiness for children of 5-6 year-old in State Kindergarten in Pekanbaru (motoric physical, emotional social, moral, language, and cognitive aspects). The population in this research is all children after 5-6 years with total of 425 children and 150 children was taken as the sample. The method used is quantitative descriptive method. Data collection technique used was observation sheet. SBased on the results of data analysis, it was obtained that the percentage of all 5 aspects of school readiness in children aged 5-6 years in kindergarten in Pekanbaru: the aspect of physical motor readiness obtained equal to 68.22% belonging to high category of motoric physical readiness and smooth child is said Developing As Expectation (BSH), emotional social readiness aspect is obtained equal to 62.47% belong to high category hence emotional social readiness of child is said Develop As Expectation (BSH), moral readiness aspect is obtained as much as 63.21% belongs to high category so the moral readiness of children is said Developed As Expectation (BSH), the aspect of language readiness is 51.14% is enough category then the readiness of children language is said to Start Developing (MB) and the aspect of cognitive readiness obtained by 49.08% is sufficient then the cognitive readiness of children is said Start developing (MB).